Pengembangan Media Evaluasi Pembelajaran Games Mobile Learning Pelajaran Geografi Guna Meningkatkan Hasil Belajar Peserta Didik Kelas X IPS Di SMA Negeri 1 Jeruklegi Tahun 2020/2021 (Materi Dasar–Dasar Pemetaan, Pengindraan Jauh dan SIG) - Hikmah Dwijayanti; Singgih Prihadi; Gentur Adi Tjahjono (Universitas Sebelas Maret (UNS), 2022)
The research aims to (1) Know the feasibility of mobile learning media and (2) Know the effectiveness of the use of mobile learning media developed to improve learning outcomes for students of class X IPS at SMA Negeri 1 Jeruklegi in 2020/2021. This research method is Research and Development (R&D) or Research and Development. The software used in the evaluation development of m-learning games is Quizizz. The subject consists of material experts, media experts, educators, student assessments, interviews, observations, documentation, and tests.The results of this study are (1) Development of M-learning Learning Geography based Quizizz is declared feasible to be used in class X IPS learning at SMA Negeri 1 Jeruklegi based on the assessment results from material experts, media experts, teachers and learners respectively – each with a mode score of 4 and 5 that fall into the category of good and excellent in the Likert Scale that has qualified from the minimum limit of m-learning eligibility with a mode score of 3 that fall into the category sufficiently in the Likert Scale as determined by the researchers. (2) Determination of the use of m-learning evaluation media of Games-based Geography learning using Quizizz application is proven to be able to increase the value of pre-test post-test by 26% in experimental class and 23% in control class.Keywords : Media Evaluation Mobile Learning, Quizizz Learning Outcomes